Advances in Immunology: A Cornerstone in Diagnosis and Therapy of Merkel Cell Carcinoma - Wyatt Lydolph MD; Sai Prasad Desikan MD; Shiyu Wang MD; John Allgood MD; Charles McClains MD; Jennifer Mclaughlin MD; Raman Desikan MD (SAGE Publishing, 2022)
Merkel cell cancer (MCC) is a rare cutaneous malignancy arising from neuroendocrine cells. This rare but lethal malignancy (mortality greater than 30%) has also tripled in incidence over the last two decades. The role of immunodeficiency in pathogenesis of this rare malignancy is well established, with elucidation of viral pathogenesis by Merkel cell polyoma virus (MCPyV), a novel polyoma virus, in a majority of patients. Viral neoantigens while playing an important role in oncogenesis can also aid in early immunologic detection of recurrent disease. Viral neoantigens can also be targets for immunotherapy. Immune checkpoint inhibitors (ICI) have established role in frontline therapy in addition to recurrence of metastatic MCC. ICI therapy is being explored in adjuvant and neoadjuvant settings as well. We would like to illustrate curative potential of early diagnosis of recurrence and prompt use of ICI in treatment of oligometastatic disease in our case presentation.